Physiological alteration of swine matrices created in the climatic semiarid conditions of Minas Gerais - Soares, Thaís Emanuele; Siqueira Carvalho, Cinara da Cunha; de Albuquerque Maranhão, Camila Maida; da Silva, Geruza Cardoso; Diniz, Thamara Amaral; Borges Pereira, Kátia Cristiane; Magalhães Gonçalves, Maria Cecilia (Revista de Ciências Agroveterinárias, 2017)
The swine breeding in the Minas Gerais semiarid has an initial characterization, but there are prospects for growth, however due to the high temperatures verified throughout the year, production is reduced. Therefore, the objective of this work was to evaluate the effect of the climatic environment on the physiological parameters of swine matrices before and after farrowing. The experiment was carried out in a representative swine breeding farm located in the region of the Gorutuba Project, in Nova Porteirinha city, MG. Six swine matrices housed in individual bays were used. The climatic variables, air temperature, relative air humidity, dew point temperature and black globe temperature were monitored through the use of two dataloggers. The physiological parameters evaluated were: body surface temperature, respiratory rate, heart rate and rectal temperature. The environmental and physiological variables were collected at 8am, 11am, 01pm, 03pm and 05pm. Data was submitted to analysis of variance, and when significant were submitted to the Tukey test at 5% probability for comparison between the means. With the data collected, it was observed that between 01pm and 05pm h and during the post-partum period, the animals were exposed to the thermal discomfort of the environment, being the responsible factor for the alteration in the respiratory rate, especially when associated with the ingestion of foods. The mean values (p<0.05) of body and rectal surface temperature were higher in the postpartum period, but did not express thermal discomfort of the swine matrices. The raising of these animals in the semiarid Minas Gerais is possible; however, it is necessary to adopt measures such as the use of ventilators and the use of curtains to minimize the animal’s caloric stress.